Цілепокладання як основа соціального проектування: праксеологічний підхід - Бірюкова, Марина Василівна (НТУ "ХПІ", 2016)
У статті досліджуються базові складові соціального проектування, заснованого на праксеологічних засадах. Особливу увагу приділяється цілепокладанню, під час якого обирається мета та завдання проекту. Праксеологічні засади соціального проектування дозволяють висунути соціальну гармонію як мету, а нарощування соціального капіталу як завдання. В структурі соціального капіталу введено новий його різновид, а саме технологічний капітал.

The article examines the basic elements of social engineering based on praxeological basis. Particular attention is paid to the goal-setting in the process of which is elected by the purpose and objectives of the project. Praksiologichnye base social planning allow us to propose social harmony as the goal, and build social capital as a problem. There are economic, political, family, religious, scientific, environmental, professional responsibilities in the field of implementation of the activities of the subject. Within each of the responsibility exists a legal and moral aspect. The social capital introduced a new structure of its kind, namely technological capital.
Targeting is the basis of social engineering: praxeological approach
Keywords: соціальний капітал; соціальна гармонія; пізнання; технологічний капітал; перспективні ціліі; раціональність; social engineering; praxeological approach; social capital; social harmony